The influence of job satisfaction, perceived organizational support, transformational leadership on employee commitment to change - Zhou, Chen Chen (2020)
Nowadays, the industrial technology or development mode of the company needs to be improved and transformed. Technological innovation and the application of intelligent logistics affected the employee commitment to change. This study attempted to investigate the factors that influence employees' commitment to change in the context of China's rapidly developing logistics industry. The variables involved in this study are job satisfaction, perceived organizational support, and transformational leadership on employee commitment to change. A total of 420 questionnaires were distributed to the express delivery industry employees in Wuhu, Anhui, China, of which only 292 were useable. The data was collected through selfadministered questionnaires by using simple random sampling. This study used Statistical Package for the Social Sciences (SPSS) to validate the developed hypotheses. The results show that job satisfaction, perceived organizational support, and transformational leadership have a positive correlation with employee commitment to change. Of all the independent variables, transformational leadership has the most significant effect on employee commitment to change. A conclusive summary is provided along with a contributive discussion. Implications and contributions to researchers and managers are discussed, and recommendations are offered. Also included are conclusive final thoughts accompanied by the limitations of this study.